Prevalência da retinopatia diabética em unidades básicas de saúde de São José do Rio Preto-SP - Cury Junior, Carlos Eduardo (2010)
Diabetic retinopathy (DR) is one of the most frequent causes of legal blindness worldwide and the most common microvascular complication of the disease. During the first two decades, almost all patients of type I and more than 60% of the patients of type II have developed the disease. Studies to determinate the prevalence of DR in a certain population are an important measure to delineate screening programs. Objective: To determine the prevalence of Diabetic Retinopathy in public health care units of São José do Rio Preto-SP-Brazil. Material and methods: Population-based cross-sectional study. The study sample, of 710 patients, was derived from the HIPERDIA (Diabetes and High-blood pressure social health care program) of São José do Rio Preto. Participants were also interviewed and examined to determine their demographic characteristics, medical conditions and the realization of previous fundoscopic eye examination All patients, known to have diabetes, underwent an eye examination by indirect ophthalmoscope to check for any signs of DR through dilated pupils.. Statistical studies were done with t-Student test, Fisher test or chi-square test.. Results: The prevalence of DR were 16,3%. Patients were divided in two groups: Group I, patients with DR 112 (16,3%) and Group II , patients without microvascular complication of diabetes 597 (83,7%) . In Group I 90 (80,4%) demonstrated non-proliferative and (22) 19,6% with proliferative diabetic retinopathy. Only 143 patients (68,7%) had a history of previous fundoscopic eye examination. Conclusions: The prevalence of DR in São José do Rio Preto is 16,3%. The main risk factors associated with DR were time of disease and glicemic control. Type of DM and nephropathy were considered secondary risk factors. The presence of high blood pressure, in this study, was not a risk factor associated with DR.